Wearable, stable, highly sensitive hydrogel–graphene strain sensors - Lv, Jian; Kong, Chuncai; Yang, Chao; Yin, Lu; Jeerapan, Itthipon; Pu, Fangzhao; Zhang, Xiaojing; Yang, Sen; Yang, Zhimao (Beilstein Journal of Nanotechnology, 2019)
A stable and highly sensitive graphene/hydrogel strain sensor is designed by introducing glycerol as a co-solvent in the formation of a hydrogel substrate and then casting a graphene solution onto the hydrogel in a simple, two-step method. This hydrogel-based strain sensor can effectively retain water in the polymer network due to the formation of strong hydrogen bonding between glycerol and water. The addition of glycerol not only enhances the stability of the hydrogel over a wider temperature range, but also increases the stretchability of the hydrogel from 800% to 2000%. The enhanced sensitivity can be attributed to the graphene film, whereby the graphene flakes redistribute to optimize the contact area under different strains. The careful design enables this sensor to be used in both stretching and bending modes. As a demonstration, the as-prepared strain sensor was applied to sense the movement of finger knuckles. Given the outstanding performance of this wearable sensor, together with the proposed scalable fabrication method, this stable and sensitive hydrogel strain sensor is considered to have great potential in the field of wearable sensors.
Keywords: graphene; high sensitivity; hydrogel; strain sensor; wearable sensor